2018
DOI: 10.1101/448100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occurrence of ordered and disordered structural elements in postsynaptic proteins supports optimization for interaction diversity

Abstract: The human postsynaptic density is an elaborate network comprising thousands of proteins, playing a vital role in the molecular events of learning and the formation of memory. Despite our growing knowledge of specific proteins and their interactions, atomic-level details of their full three-dimensional structure and their rearrangements are mostly elusive. Advancements in structural bioinformatics enabled us to depict the characteristic features of proteins involved in different processes aiding neurotransmissi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The role of postsynaptic density (PSD) proteins in neural degeneration is often revisited in various papers 44,45 . In our recent article, we showed that postsynaptic density proteins are exceptionally modular, and they are highly enriched in coiledcoil regions 46 . These results further underline the critical role of coiled-coil containing proteins in the PSD, and advocates the importance of modular protein structures in disease development.…”
Section: Discussionmentioning
confidence: 99%
“…The role of postsynaptic density (PSD) proteins in neural degeneration is often revisited in various papers 44,45 . In our recent article, we showed that postsynaptic density proteins are exceptionally modular, and they are highly enriched in coiledcoil regions 46 . These results further underline the critical role of coiled-coil containing proteins in the PSD, and advocates the importance of modular protein structures in disease development.…”
Section: Discussionmentioning
confidence: 99%
“…PSD proteins exhibit a high degree of multivalency presenting multiple binding sites stacked into single proteins. This multivalency aids the formation of an elaborate and dynamic network via highly modular architecture, provided by distinct structural and functional elements [7]. Intrinsically disordered regions (IDRs) were shown to be critical components for network assembly in the PSD [8], often by containing short linear motifs mediating transient interactions [9], post-translational modification sites regulating interactions as switches [10] and more.…”
Section: Introductionmentioning
confidence: 99%